2011
DOI: 10.1097/jom.0b013e31821ad5f1
|View full text |Cite
|
Sign up to set email alerts
|

A Small Business Approach to Nanomaterial Environment, Health, and Safety

Abstract: Understanding and managing potential hazards to our nanotechnology workers is key to the success and acceptance of nanotechnology enabled products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The study by Gause et al . [16] reported a surveillance program in a small business in the USA with approximately 200 workers of which 20% were exposed to ENMs. One study initially reported findings from 2012 [22], with 20 exposed workers (16 in production and 4 in research positions) and 20 control participants, as well as, findings from 2013, with 28 exposed workers (14 in production and 14 in office positions) and 25 control participants [22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Gause et al . [16] reported a surveillance program in a small business in the USA with approximately 200 workers of which 20% were exposed to ENMs. One study initially reported findings from 2012 [22], with 20 exposed workers (16 in production and 4 in research positions) and 20 control participants, as well as, findings from 2013, with 28 exposed workers (14 in production and 14 in office positions) and 25 control participants [22].…”
Section: Resultsmentioning
confidence: 99%
“…One study was a case study [17], three were cross-sectional in design [18,20,21], one was stated as longitudinal, but was a follow-up cross sectional study [19] and one study was a case study that reported results pre- and post-shift exposure [23]. One study was conducted in Virginia, United States [16], one in the Czech Republic [23], three in Taiwan [18,19,20] and two in South Korea [17,21]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of current medical surveillance were described in a variety of industrial and academic contexts. [27][28][29] The concerns raised at the conference about the limitations of medical surveillance with present technology, while important to address, do not outweigh the future benefits that detailed worker registries will accrue, namely aid to epidemiologists in rapidly addressing type 1, 2, and 3 disasters. Finally, we must keep in mind that populations other than workers may experience significant exposure in the future, so that proactive monitoring now may pay great dividends as ENM proliferate in society.…”
mentioning
confidence: 99%